Does the RGD region of certain proteins affect metabolic activity? - Karin Nagasaki; Karin Nagasaki; Oksana Gavrilova; George Hajishengallis; Martha J. Somerman (Frontiers Media S.A., 2022)
A better understanding of the role of mineralized tissues and their associated factors in governing whole-body metabolism should be of value toward informing clinical strategies to treat mineralized tissue and metabolic disorders, such as diabetes and obesity. This perspective provides evidence suggesting a role for the arginine-glycine-aspartic acid (RGD) region, a sequence identified in several proteins secreted by bone cells, as well as other cells, in modulating systemic metabolic activity. We focus on (a) two of the SIBLING (small integrin-binding ligand, N-linked glycoprotein) family genes/proteins, bone sialoprotein (BSP) and osteopontin (OPN), (b) insulin-like growth factor-binding protein-1 & 2 (IGFBP-1, IGFBP-2) and (c) developmental endothelial locus 1 (DEL1) and milk fat globule-EGF factor-8 (MFG-E8). In addition, for our readers to appreciate the mounting evidence that a multitude of bone secreted factors affect the activity of other tissues, we provide a brief overview of other proteins, to include fibroblast growth factor 23 (FGF23), phosphatase orphan 1 (PHOSPHO1), osteocalcin (OCN/BGLAP), tissue non-specific alkaline phosphatase (TNAP) and acidic serine aspartic-rich MEPE-associated motif (ASARM), along with known/suggested functions of these factors in influencing energy metabolism.